Judas - dall'Antonia, Lara; Wingate, Ann; Fantana, Tom; Carner, Charles Robert (Hollywood, California : Paramount Pictures, 2004)
Judas meets Jesus and at first doesn't know what to make of him or whether or not to trust him. A cynical city boy, Judas makes fun of the country bumpkin disciples who follow Jesus but eventually decides to join the band, as well. He and Jesus become good friends, even though they often see things very differently. Ultimately, Judas is convinced that Jesus needs to use his popularity and wonder-working powers to free the Jews from the Romans, and Jesus sees a larger, spritual perspective. As a friend, Judas convinces Jesus to give his disciples his miraculous powers, and he does with good results. Finally, the Jewish leaders spy on Judas and convince him of the greater good of betraying Jesus, in order to save the Jewish people. Judas gets caught between the corrupt leaders, Caiaphus and Pontius Pilate, and Jesus
Title from title screen
executive produser Frank R. Desiderio, Tom Fontana
Cast: Johnathon Schaech, Jonathan Scarfe, Tim Matheson, Fiona Glascott, Owen Teale, Bob Gunton, Mark Womack, Rory Kinnear, Enzo Squillino Jr., Suzanne Bertish, Harry Peacock, Paul Haigh, Georgia Mackenzie, Elliot Levey, Danny Scheinmann
DVD Format
Dolby digital
in English with optional English or Korean subtitles
Keywords: Judas Iscariot -- Drama; Jesus Christ -- Crucifixion -- Drama; Betrayal -- Drama